1977
DOI: 10.1139/f77-117
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Methods for Determining Temperature Preference

Abstract: Different types of temperature-gradient devices used in the laboratory to determine temperature preferences of fish are classified and reviewed. The type of device used seems to have less effect on experimental results than do other variables such as age, size, season, physiological state, or social interactions. Key words: preferred temperature, thermal gradients, thermoregulation, behavioral, gradient devices, laboratory techniques

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

1977
1977
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 0 publications
2
33
0
1
Order By: Relevance
“…The chamber is a modified version of a behavioral trough used for olfactory preference experiments by Jones & Hara (1985). Water flow was perpendicular to the axis of the gradient; this eliminated bias due to rheotactic behavior induced by horizontal gradients that utilize along-axis flow to establish the gradient (McCauley 1977, Coutant et al 1984.…”
Section: Experimental Apparatus and Techniquementioning
confidence: 99%
“…The chamber is a modified version of a behavioral trough used for olfactory preference experiments by Jones & Hara (1985). Water flow was perpendicular to the axis of the gradient; this eliminated bias due to rheotactic behavior induced by horizontal gradients that utilize along-axis flow to establish the gradient (McCauley 1977, Coutant et al 1984.…”
Section: Experimental Apparatus and Techniquementioning
confidence: 99%
“…Peterson et al 1979. Edsall and Clelland 2000 and shuttle boxes that produce a varying thermal gradient controlled by the organisms' movement (McCauley 1977, Konecki et al 1995 have traditionally been employed to measure thermal preference. However, thesc test systems may be limited by the presence of confounding variables inherent to their design such as varying water depth.…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial and aquatic vertebrates and invertebrate poikilothermic species have been shown to possess distinct thermal range preferences (Crawshaw, 1974;Mathur et al, 1982;Mathur & Silver, 1980;McCauley, 1977;Richards et al, 1977;Stauffer et al, 1975). Fry (1947) defined the final thermal preferendum as the temperature "around which all individuals will congregate regardless of their thermal experience prior to placement in the gradient" and as ''that temperature at which the preferred temperature is equal to the acclimation temperature".…”
Section: List Of Tablesmentioning
confidence: 99%